ELA Useful in Treatment of Femoropopliteal ISR - Hoyle, Brian (MD Conference Express, 2014)
Use of excimer laser atherectomy (ELA) as an adjunct to percutaneous transluminal angioplasty (PTA, also known as balloon angioplasty) is superior to PTA alone in patients with peripheral artery disease who experience artery narrowing following stent implantation (in-stent restinosis [ISR]). This article discusses the results from the Randomized Study of Laser and Balloon Angioplasty Versus Balloon Angioplasty to Treat Peripheral In-Stent Restenosis [EXCITE ISR; NCT01330628].